Peningkatan kualitas Media Pembelajaran dengan Google sites pada guru SMK 1 Windusari Magelang - Rofi Abul Hasani; Uky Yudatama; Resa Arif Yudianto; Pristi Sukmasetya; Maimunah Maimunah (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
Technology has changed the teaching and learning process in the world of education. The most visible change is the use of learning media in schools. The presence of digital media provides a variety of educational innovations, where rigid and monotonous conventional learning will be replaced by learning using digital media which is considered more practical, flexible, and not limited by space and time. One of the learning media is a website. Based on the results of interviews with teachers at SMK Negeri 1 Windusari, they said the importance of online learning media, especially when online learning demands. Therefore, in this PKM, the authors carry out google sites training activities to improve the ability of teachers of SMK Negeri 1 Windusari to create learning media. After training on making teaching media using google sites will help teachers in making interesting learning materials and conveying them to students. So that this activity will provide good benefits to teachers, students, and SMK N 1 Windusari, Magelang Regency. Many teachers were previously reluctant to use making websites because of difficulties. However, after this training, the teachers at SMK Negeri 1 Windusari began to be enthusiastic about making learning media using google sites. Because using google sites is quite easy for teachers to do. Keywords: Google Site, Learning Media, Teacher, Website